LEGAL FRAMEWORK IN THE FULFILMENT OF RIGHT TO EDUCATION AS CONSTITUTIONAL RIGHT OF CITIZENS IN BORDER AREA OF NUNUKAN-NORTH KALIMANTAN PROVINCE (Comparison Study and Legal Framework of Right to Education of Citizens in Border Area of Indonesia-Sabah, Malaysia) - Zein, Yahya Ahmad; Syaprillah, Aditia; Rohman, Arif (Tadulako Law Review, 2017)
The issues was found based on research results in the first year of the model of the fulfillment of the right to education as a constitutional right of citizens in the Nunukan-North Kalimantan Province. The research addresses the policies and models of the fulfillment of the right to education there are still various weaknesses, especially related to the implementation of policies has been contained in the Local Regulations, even worsened by the neglect of border area management principles based on the fulfillment of the right to education that will break the poverty chain, and will strengthen the orientation of border area management based on the welfare of the people. This is of course very interesting when compared to Malaysia's neighboring state Sabah in the fulfillment of the right to education concerning the availability, affordability, acceptance, and conformity of education.The main issues be discussed in this study are how is comparative policies and how os comparison of the framework in the fulfillment of the right to education as a constitutional right of citizens in the border region of Nunukan Indonesia and Sabah Malaysia.this research is a comparative law study so that it will provide a new policy model of border area management based on the fulfillment of the right to education.The results of this study conclude that the Malaysian government's policy of opening and developing the port of Tawau at the end of the 19th century and the port of Tawau is the third major destination in Sabah after Kota Kinabalu and Sandakan as evidence that the management of its border areas using the prosperity approach has brought prosperity to Malaysian citizen who is on the border of his country and this is directly proportional to the strengthening of human resources through the Infrastructure and quality of education of his country. The results of the Model comparison indicate that there are significant differences in the fulfillment of the right to education as a constitutional right of citizens in the border regions of Nunukan Indonesia and Sabah Malaysia in terms of the conditions of educational infrastructure and access to education information. Affordability of school locations and systems that facilitate the process towards educational facilities.Availability of quality education standards for citizens and the availability of adequate teachers at every level of education.The aim of this research is not only for the development of science, especially the knowledge of Indonesian border region, but also contributes as a reference for the government related to the policy of border area management in Indonesia, particularly the reference for Local Govenrmment of Nunukan.